Pengaruh Model Pembelajaran Inkuiri Terbimbing Terhadap Minat Belajar Biologi Siswa Lintas Minat - Lisnawati, Lisnawati; Rambitan, Vandalita; Candra, Candra (FKIP Universitas Lampung, 2018)
The Influence of Guided Inquiry Learning Model toward The Interest of Learning Study of Biology Student Cross-Interest. This quasy Experiment research aims to determine the influence of guided inquiry learning model toward the interest of biology students learning cross-interest involving 66 high school students in Tenggarong Seberang. The research design used non-equivalent pretest-posttest control group design. The data analysis of the increase ofstudents’ learning interest in the application of this learning model was obtained from the mean of N-Gain, while the influence of inquiry learning model was guided against the interest of learning done through t-test for normal distributed data and U Mann-Whitney U test for abnormally distributed data. Based on data analysis, it was found that biology learning interest score after learning process in experiment and control class was significantly different (sig. (2- tailed) <0.05). In addition, there was an increase in student interest in the low category but significantly different (U test = 257.0 <Utabel = 818). Keyword: Guided inquiry, cross-interest, interest in learning.DOI: http://dx.doi.org/10.23960/jpp.v8.i1.201803